A randomised controlled trial of the effects of albendazole in pregnancy on maternal responses to mycobacterial antigens and infant responses to bacille Calmette-Guérin (BCG) immunisation [ISRCTN32849447] - Elliott, A; Namujju, P; Mawa, P; Quigley, M; Nampijja, M; Nkurunziza, P; Belisle, J; Muwanga, M; Whitworth, J (BioMed Central, 2005)
Background: Maternal schistosomiasis and filariasis have been shown to influence infant responses to neonatal bacille Calmette-Guérin (BCG) immunisation but the effects of maternal hookworm, and of de-worming in pregnancy, are unknown. Methods: In Entebbe, Uganda, we conducted a randomised, double-blind, placebo-controlled trial of a single dose of 400 mg of albendazole in the second trimester of pregnancy. Neonates received BCG. Interferon-gamma (IFN-γ) and interleukin (IL)-5 responses to a mycobacterial antigen (crude culture filtrate proteins (CFP) of Mycobacterium tuberculosis) were measured in a whole blood assay. We analysed results for binary variables using χ2 tests and logistic regression. We analysed continuous variables using Wilcoxon's tests. Results: Maternal hookworm was associated with reduced maternal IFN-γ responses to CFP (adjusted odds ratio for IFN-γ > median response: 0.14 (95% confidence interval 0.02–0.83, p = 0.021). Conversely, maternal hookworm was associated with subsequent increased IFN-γ responses in their one-year-old infants (adjusted OR 17.65 (1.20–258.66; p = 0.013)). Maternal albendazole tended to reduce these effects. Conclusion: Untreated hookworm infection in pregnancy was associated with reduced maternal IFN-γ responses to mycobacterial antigens, but increased responses in their infants one year after BCG immunisation. The mechanisms of these effects, and their implications for protective immunity remain, to be determined.